Investor Memory and Biased Beliefs: Evidence from the Field - Zhengyang Jiang; Hongqi Liu; Cameron Peng; Hongjun Yan (The Quarterly Journal of Economics, 2025)
Abstract We survey a large, representative sample of retail investors in China to elicit their memories of stock market investments and their return expectations. We merge these survey data with administrative transaction data to test a model in which investors selectively recall past experiences to form their beliefs. Our analysis uncovers new facts about investor memory and highlights similarity-based recall as a key mechanism of belief formation in financial markets. A rising market prompts investors to recall their past experiences more positively, leading to more optimistic forecasts of future returns. Recalled experiences can explain cross-investor variation in return expectations and, in our setting, dominate actual experiences in their explanatory power. In the transaction data, we confirm that recalled experiences are reflected in investors’ trading decisions through a belief channel.